การพัฒนาหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว กลุ่มสาระการเรียนรู้วิทยาศาสตร์ เรื่อง โลกและการเปลี่ยนแปลง สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 5 - ทรงช่วง, จุฑามาศ; เล็กศิริรัตน์, พฤฒิพงษ์; สร้อยเพชรเกษม, ชัยลิขิต (JOURNAL OF SOUTHERN TECHNOLOGY, 2013)
งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว กลุ่มสาระการเรียนรู้วิทยาศาสตร์ เรื่อง โลกและการเปลี่ยนแปลง สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 5 ให้มีประสิทธิภาพตามเกณฑ์มาตรฐาน 80/80 หาดัชนีประสิทธิผลของหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว เปรียบเทียบผลสัมฤทธิ์ทางการเรียนหลังเรียนของนักเรียนระหว่างกลุ่มที่เรียนด้วยหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหวกับกลุ่มที่เรียนด้วยวิธีการเรียนแบบปกติและศึกษาความพึงพอใจของนักเรียนที่มีต่อหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว กลุ่มตัวอย่างที่ใช้ คือนักเรียนชั้นมัธยมศึกษาปีที่ 5 โรงเรียนหาดใหญ่วิทยาลัยสมบูรณ์กุลกันยา ภาคเรียนที่ 2 ปีการศึกษา 2555 จำนวน 102 คน โดยใช้วิธีการสุ่มกลุ่มและแบ่งชั้นภูมิ เครื่องมือที่ใช้ในงานวิจัยได้แก่ 1) หนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว 2) แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียนมีค่าความเชื่อมั่นเท่ากับ 0.75 3) แบบสอบถามความพึงพอใจของนักเรียนที่มีต่อหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว 4) แบบประเมินคุณภาพหนังสืออิเล็กทรอนิกส์และ 5) แผนการจัดการเรียนการสอน สำหรับสถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และการวิเคราะห์ความแปรปรวนหลายทางแบบวัดซ้ำ ผลการวิจัยพบว่า 1) หนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหวมีประสิทธิภาพเท่ากับ 83.57/85.57 2) หนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหว มีค่าดัชนีประสิทธิผลเท่ากับ 0.62 3) ผลสัมฤทธิ์ทางการเรียนหลังเรียนของนักเรียนระหว่างกลุ่มที่เรียนด้วยหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหวสูงกว่านักเรียนกลุ่มที่เรียนด้วยวิธีการเรียนแบบปกติ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 4) ความพึงพอใจของนักเรียนที่มีต่อหนังสืออิเล็กทรอนิกส์แบบภาพเคลื่อนไหวอยู่ในระดับมาก The Development of a Motion Picture Electronic Book on the Topic of the Earth and the Changes in the Science Subject for Grade 11 Students The objectives of this research were 1) to develop a motion picture electronic book on the topic of the earth and the changes in the science subject for grade 11 students to meet the standard criteria of 80/80, 2) to identify the effectiveness index of the developed motion picture book, 3) to compare the academic achievement of the students who were taught using the developed electronic book and those with the conventional technique, and 4) to study the students’ satisfaction with the developed motion picture electronic book. The sample consisted of 102 grade 11 students attending Hatyaiwitthayalaisomboonkulkanya School during the second semester of the 2012 academic year. They were drawn using cluster and stratified sampling techniques. The instruments used in the study consisted of 1) the motion picture electronic book, 2) an achievement test with .75 reliability coefficient, 3) a students’ satisfaction questionnaire, 4) an evaluation form probing the efficiency of the motion picture electronic book and 5) the lesson plans on the topic of the earth and the changes. The percentage, arithmetic means, standard deviation and repeated measure factorial ANOVA were used in the data analysis process. The findings revealed the following. 1) The motion picture electronic book showed the effectiveness of 83.57/85.57. 2) The motion picture electronic book showed the effectiveness index of 0.62. 3) The achievement of the students who were taught with the motion picture electronic book was .05 significantly higher than those taught with the conventional method. 4) The students had a high level of satisfaction with the motion picture electronic book.